Tracing hydrosocial change: the social constellations of water access and allocation for oil and gas development in Colorado - Boone, Karie, author; Laituri, Melinda, advisor; Carolan, Michael, committee member; Hempel, Lynn, committee member; Poff, LeRoy, committee member (Colorado State University. Libraries, 2018)
Increasing water use for OG development in Colorado suggests a change in the social constellations of water governance. Colorado's water allocation institutions, practices and policies relationally shape and are shaped by water's biophysical movement over space and time through a hydrosocial cycle. The hydrosocial cycle (HSC) framework examines social complexity of water governance institutions by systematically analyzing institutional change and continuity to identify the causes and consequences of decreasing agricultural water access. Starting with history, change and continuity are operationalized through a historical institutional framework that systematically pinpoints institutional outcomes resulting from a particular sequence of events, policies and practices occurring in a unique context. This historical institutional analysis finds that social complexity can be measured more accurately by attending to relational and informal institutions, operationalizing the HSC framework to address ambiguities between historical policy and contemporary practices. To capture social complexity, then, this research considers how objects in nature and society are relational so that their meanings and uses depend on human agency and context. Colorado's institution of water rights is relational in two crucial ways. First, formal institutions are shaped by their social, political, and environmental settings/contexts. Concomitantly, formal institutions are shaped by processes and interactions that link Colorado's energy and water institutions across policy topics and levels of government instead of viewing them as evolving in isolation. A hydrosocial analysis additionally captures social complexity of water institutions through an examination of the often overlooked informal social processes occurring 'under the surface'. Informal institutions are nuanced norms, decision-making structures, unwritten rules and activities that shape and are shaped by agent's lived experiences. These informal dealings are consistently negotiated day-by-day, are not defined in formal laws, policies or organizational documents but help explain formal institutional change and actual policy outcomes. The integration of informal and relational institutions links the hydrological and social while further enriching our understanding of how increasing water use for OG extraction shapes agricultural water access and allocation in Colorado's rural communities. The changing nature of water use is taking place in Colorado's rural agricultural regions and in appropriated river basins, the Colorado River in the western part of the state and the South Platte River Basin flowing through the eastern plains. This dissertation asks if agricultural water users in these basins and in Colorado's top OG producing regions, Weld and Garfield Counties, are experiencing changes in water access related to increased water use for OG development. It additionally examines the implications of these changes. Each of the following chapters addresses this question while making theoretical and conceptual contributions to the HSC framework. The first two chapters utilize a comparative case study methodology to provide in-depth examination of the 'how' and 'why' of historical and political change processes, an important step in building understanding of Colorado's changing agricultural water allocation and access. A historical institutional analysis finds that social complexity can be measured more accurately by attending to relational and informal institutions. Chapter two examines relational and informal institutions from the perspective of water users on the ground and in the field. Interviews qualitatively investigate if agricultural water users are experiencing changes in water access related to increased water use for OG. In response, four primary themes emerged from an analysis of interview data: decreasing and differential water access for producers, leasing land and water from municipal and industrial users, maintaining agricultural water rights, and balancing equity in water access. Findings illuminate the important and changing role Agricultural Water Supply Organizations (AWSOs ) play in balancing equity in and maintaining water access for agricultural users. Chapter three suggests attending to increasing social distance in the U.S, including the rural-urban divide, by infusing policies with rural understandings. An embodied and inclusive pedagogy encourages empathy so that fewer political divides surface when rural communities feel silenced and forgotten. Interdisciplinary learning paradigms should work to generate empathy so that urban-biased water policies and practices infuse understanding across difference and foster social cohesion